2021
DOI: 10.3389/fonc.2021.798832
|View full text |Cite
|
Sign up to set email alerts
|

Combined Stereotactic Body Radiotherapy and Immunotherapy Versus Transarterial Chemoembolization in Locally Advanced Hepatocellular Carcinoma: A Propensity Score Matching Analysis

Abstract: Immunotherapy has achieved modest clinical activity in HCC patients. Propensity score matching analysis was conducted to compare the efficacy and safety of combined stereotactic SBRT-IO versus TACE in patients with locally advanced HCC in a tertiary center of Hong Kong. Patients with locally advanced HCC who were medically inoperable for, refractory to, or refused to curative surgical interventions were eligible. The primary outcome was PFS; the secondary outcomes were OS, ORR as per mRECIST version 1.1, and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…It is important to investigate the individual basis of prognostic factors and treatment options for these groups. More and more published studies have demonstrated the beneft of integrating SBRT with other treatment modalities [8][9][10]. We established and validated a nomogram to show these patients' 6-, 12-, and 18-month post-SBRT survival probabilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to investigate the individual basis of prognostic factors and treatment options for these groups. More and more published studies have demonstrated the beneft of integrating SBRT with other treatment modalities [8][9][10]. We established and validated a nomogram to show these patients' 6-, 12-, and 18-month post-SBRT survival probabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that in HCC patients with regional lymph node or distant metastases, combined SBRT of the intrahepatic HCC lesions demonstrated superior survival OS compared to those treated systemically only [ 9 ]. In addition, the combination of SBRT and immunotherapy achieved favorable control (CR rate: 50%) in patients with BCLC-C HCC, even though only a nonablative dose of radiation was delivered because of the extensive tumor burden [ 10 ]. SBRT sequenced with systemic or TACE was conditionally recommended for patients with BCLC-C HCC by some clinical evidence-based treatment guidelines [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yttrium-90 radioembolization (Y-90 RE) plus immunotherapy was safe and effective in patients with advanced HCC, with an objective response rate of 31% ( 38 ). The combination of radiotherapy and immunotherapy in patients with HCC showed 1- and 2-year PFS of 93.3% and 77.8%, respectively ( 39 ). A phase I trial reported that radiotherapy plus ipilimumab had clinical benefits in 23% of patients with liver/lung cancer ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additional radiotherapy did not increase the side effects in our case. A previous study suggested that radiotherapy plus immunotherapy did not cause radiation-induced liver disease and treatment-related deaths ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a study by Chiang et al described higher ORR in ve patients with unresectable, large HCC, treated with RT plus ICIs 17 . They further investigated 15 patients with advanced HCC who had a better prognosis after treatment with RT-ICIs than that with TACE 32 . In addition, treatment of a case with macroscopic vascular invasive HCC with Y-90 radioembolization plus nivolumab successfully decreased the extent of treatment to partial hepatectomy 33 .…”
Section: Discussionmentioning
confidence: 99%